Adrenergic C1 neurons monitor arterial blood pressure and determine the sympathetic response to hemorrhage - George M.P.R. Souza; Ruth L. Stornetta; Daniel S. Stornetta; Patrice G. Guyenet; Stephen B.G. Abbott (Cell Reports, 2022)
Summary: Hemorrhage initially triggers a rise in sympathetic nerve activity (SNA) that maintains blood pressure (BP); however, SNA is suppressed following severe blood loss causing hypotension. We hypothesized that adrenergic C1 neurons in the rostral ventrolateral medulla (C1RVLM) drive the increase in SNA during compensated hemorrhage, and a reduction in C1RVLM contributes to hypotension during decompensated hemorrhage. Using fiber photometry, we demonstrate that C1RVLM activity increases during compensated hemorrhage and falls at the onset of decompensated hemorrhage. Using optogenetics combined with direct recordings of SNA, we show that C1RVLM activation mediates the rise in SNA and contributes to BP stability during compensated hemorrhage, whereas a suppression of C1RVLM activity is associated with cardiovascular collapse during decompensated hemorrhage. Notably, re-activating C1RVLM during decompensated hemorrhage restores BP to normal levels. In conclusion, C1 neurons are a nodal point for the sympathetic response to blood loss.